The toxicity of human lung epithelial cells exposure to PM2.5 and glucose before or after intervention of Guilu Erxian Jiao - Tseng, Wei-Jung; Eboña, Kurt Russ; Lien, Szu Han; Tayo, Lemmuel L.; Tsai, Jen Hsiung; Lu, Jian He; Wang, Chih Lung; Chao, How Ran; Lin, Sheng Lun; Jiang, Jheng-Jie; Jalaludin, Juliana (AAGR Aerosol and Air Quality Research, 2024)
PM2.5 is known to be a potential risk factor for the progression of diabetes, particularly type 2 diabetes (T2D). Guilu Erxian Jiao (GEJ), a traditional Chinese medicine containing deer antlers and turtle shells, has been shown to have multiple health benefits. Given the synergistic association between PM2.5 levels and T2D prevalence, as well as the therapeutic properties of GEJ, this study used treatment of PM2.5 and glucose to assess the mitigating effects of GEJ intervention in A549 cells. This study aimed to mimic the effects of a GEJ intervention on cell growth, cell death, wound healing, and oxidative stress after T2D patients’ exposure to PM2.5. Our findings showed that A549 cells exposure to PM2.5 or glucose led to a significant decrease in cell growth, an increase in cell death, and impaired wound healing, even at low levels of PM2.5 (10 µg mL–1 ) and glucose (20 mM). Cotreatment with PM2.5 and glucose at 50 µg mL–1 and 120 mM, respectively, exacerbated these effects. The administration of 200 µg mL–1 GEJ resulted in the most significant improvement, regardless of the presence of PM2.5 or glucose treatment. GEJ was revealed to upregulate antioxidant genes in A549 cells, such as MnSOD and CAT, indicating its potential radical-scavenging effects in cells treated with PM2.5 and glucose. The findings also revealed that cotreatment with high levels of PM2.5 and glucose in A549 cells leads to more severe health consequences, including reduced cell growth (decreased by 1.65–2.32%), increased cell death (increased by 4.8%–7.2%), impaired wound healing (reduced by –14–5.0%), and upregulation of reactive oxygen species. In contrast, GEJ intervention helped repair cellular damage (repaired by 3.2–7.9%), improving the wound healing rate from 51% to 63%. GEJ might have the potential to modulate oxidative stress and ameliorate the effects of high PM2.5 and glucose.